Factors influencing adherence to lifestyle prescriptions among patients with nonalcoholic fatty liver disease: A qualitative study using the health action process approach framework - Lina Wang; Huixuan Zhou; Yali Liu; Xin Wang; Wenjing Yan; Wenjing Yan; Jing Zhang; Hong Ren (Frontiers Media S.A., 2023)
Background and objectiveLifestyle modifications aimed at weight loss have been introduced as a cornerstone of nonalcoholic fatty liver disease (NAFLD) management. However, very few patients follow the doctor's prescription to change their lifestyle to achieve weight loss in the real world. The purpose of this study was to use the Health Action Process Approach (HAPA) model to examine the factors that affect adherence to lifestyle prescriptions among patients with NAFLD.MethodsSemi-structured interviews were conducted with patients with NAFLD. Reflexive thematic analysis and framework analysis were used to determine naturally identified themes and allocate them to theoretically driven domains.ResultsThirty adult patients with NAFLD were interviewed, and the identified themes were mapped directly onto the constructs of the HAPA model. This study revealed that key barriers to adhering to lifestyle prescriptions are related to the coping strategy and outcome expectation constructs of the HAPA model. For physical activity, conditional limits, lack of time, symptoms such as fatigue and poor physical fitness, and fear of sports injury are the primary barriers. Barriers to diet are mainly diet environment, mental stress, and food cravings. Key facilitators for adherence to lifestyle prescriptions include developing simple and specific action plans, coping strategies to flexibly deal with obstacles and difficulties, receiving regular feedback from doctors to improve self-efficacy, and using regular tests and behavior recording to enhance action control.ConclusionsFuture lifestyle intervention programs should pay particular attention to the planning, self-efficacy, and action control-related constructors of the HAPA model to promote the adherence of patients with NAFLD to lifestyle prescriptions.